Fusobacterium nucleatum mechanis of action in alveolar bone destruction: Scoping review - Idrus, Erik; Shania Harsono, Tashya; Lestari, Widya; Fatma Suniarti, Dewi (Wolters Kluwer - Medknow, 2024)
Fusobacterium nucleatum is implicated in periodontitis, a chronic inflammatory disease that destroys the periodontal tissue and alveolar bone due to hostmicrobe dysbiosis. This study focuses on understanding how F. nucleatum contributes to bone destruction in periodontitis. The literature search was conducted using PubMed and Scopus databases based on Preferred Reporting Items for Systematic Review and Meta‑Analyses guidelines by entering preselected keyword combinations of inclusion and exclusion criteria. Qualifying literature was evaluated based on four inclusion criteria: research articles, published in English, within the last ten years, and available in full text. The literature search yielded five articles exploring the mechanism of bone resorption by F. nucleatum. It was found that the bacteria increases the production of inflammatory mediators, such as interleukin (IL)‑1β, IL‑6, IL‑8, tumor necrosis factor‑alpha, C‑C motif chemokine ligand (CCL) 2, CCL20, and C‑X‑C motif chemokine ligand 1, which leads to the destruction of alveolar bone. During infection, biomechanical stress also raises levels of prostaglandin E2 and cyclooxygenase-2. The elevated levels of inflammatory mediators and enzymes generate an imbalance in the receptor activator of nuclear factor kappaB ligand to osteoprotegerin ratio, hindering osteogenic differentiation and heightening bone destruction. In conclusion, F. nucleatum infection promotes alveolar bone destruction by inducing inflammatory responses and inhibiting osteogenic differentiation stimulated by biomechanical loading. More research is essential to explore the connection between F. nucleatum virulence and its alveolar bone degradation mechanisms.